2005
DOI: 10.1111/j.1472-765x.2005.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylloplane bacteria increase seedling emergence, growth and yield of field-grown groundnut (Arachis hypogaea L.)

Abstract: Aim: To isolate and characterize groundnut-associated bacterial isolates for growth promotion of groundnut in field. Methods and Results: Three hundred and ninety-three groundnut-associated bacteria, representing the geocarposphere, phylloplane and rhizosphere, and endophytes were applied as seed treatment in greenhouse. Maximum increase in plant biomass (up to 26%) was observed following treatment with a rhizosphere isolate identified as Bacillus firmis GRS 123, and two phylloplane isolates Bacillus megateriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 21 publications
4
34
0
3
Order By: Relevance
“…The two most common groundnut plant growth promoting rhizobacteria (PGPR) that enhance biomass, nitrogen and phosphorous uptake and cropyield are Pseudomonas and Bacillus sp. (Dey et al 2004;Saravanakumar and Samiyappan 2007;Kishore et al 2005). Until recently, most studies aiming for the isolation and identification of PGPR were based on cultivation and phenotypic characterization of bacterial isolates (Prosser et al 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The two most common groundnut plant growth promoting rhizobacteria (PGPR) that enhance biomass, nitrogen and phosphorous uptake and cropyield are Pseudomonas and Bacillus sp. (Dey et al 2004;Saravanakumar and Samiyappan 2007;Kishore et al 2005). Until recently, most studies aiming for the isolation and identification of PGPR were based on cultivation and phenotypic characterization of bacterial isolates (Prosser et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In rain-fed areas of Asia, soil fertility is an important constraint for high pod yields. The majority of the small-scale farmers in these regions are reluctant to invest in chemical fertilizers and other agrochemicals because of the unassured crop returns owing to the high incidence of fungal diseases and unpredictable monsoon (Kishore et al 2005). Besides, application of inorganic fertilizer debilitates the soil's physical and chemical status and drastically alters microbial diversity, which is vital to sustain the fertility of soil (Adesemoye and Kloepper 2009;Yang et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al (2011) also reported that strains MSC1 (Pseudomonas putida) and MSC4 (Pseudomonas pseudoalcaligens) showed increases in all vegetative parameters of chickpea under saline conditions. Similarly, enhancement of growth parameters of groundnut by pseudomomads has also been reported by a number of authors (e.g., Gupta et al 2002;Kishore et al 2005;Bhatia et al 2008). Recently, Stefan et al (2013) found that runner bean seed inoculation with two rhizobacterial strains resulted in an increase of photosynthetic activities, water-use efficiency and chlorophyll content along with their significant yield.…”
Section: Discussionmentioning
confidence: 73%
“…Even though the liquid form of rhizobial inoculants is applied in the production process more easily than solid form, the survival of rhizobial cell in liquid inoculants depends on strain of rhizobia and polymeric additive substance incorporated into liquid inoculants formulation (Tittabutr et al, 2007). Thus, solid inoculants, especially those using peat-based carrier, are still popular for biofertilizer inoculant production because peat could support the survival of bacteria in long term storage (Kishore et al, 2005;Okon & Labandera-Gonzalez, 1994). However, peat is limited in many countries including Thailand, so it is necessary to find carriers that are locally available for commercial scale production.…”
Section: Introductionmentioning
confidence: 99%